2007
DOI: 10.1177/073953290702800204
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anonymous Sources Declines in U.S. Newspapers

Abstract: Recent media scandals have renewed the debate about the use of anonymous sources. This content analysis shows a decline in the number of anonymous sources in 2004 compared with 2003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…13 More recent research confirmed declining use of unnamed sources in 16 different newspapers and four major network news shows. 14 Studies show that use of unnamed sources also varies by medium, topic and story magnitude. They appeared in 75 percent and 70 percent of all articles in Time and Newsweek, respectively.…”
Section: The Role Of Unnamed Sourcesmentioning
confidence: 99%
“…13 More recent research confirmed declining use of unnamed sources in 16 different newspapers and four major network news shows. 14 Studies show that use of unnamed sources also varies by medium, topic and story magnitude. They appeared in 75 percent and 70 percent of all articles in Time and Newsweek, respectively.…”
Section: The Role Of Unnamed Sourcesmentioning
confidence: 99%
“…Unnamed sourcing has been a common practice in war coverage (Denham, 1997), network news (Wulfemeyer & McFadden, 1986) and magazines providing news (Wulfemeyer, 1985). According to Martin-Kratzer and Th orson (2007), overall there was a decline in the use of unnamed sources by journalists in wire and staffproduced stories and among all circulation categories in the U.S. in 2004 compared with 2003. Although a few studies show that use of unnamed sources increased in the early 1980s (e.g.…”
Section: Unnamed Sourcing For Newsmentioning
confidence: 99%
“…18 A consistent theme of this research is that journalists have a clear preference for citing sources that occupy positions of power within formal institutions or that represent influential segments of society. 18 Specifically, these studies have shown that while journalists occasionally reference a diverse array of actors in their reporting, including interest groups, 19 anonymous individuals 21 and policy experts, 22 a small group of government sources dominate most political reporting. 23 For many observers, this "limited diversity" 24 in sources is problematic given that it expands elite control over the media's agenda and limits the number of perspectives heard by the public.…”
Section: Source Diversity Is a Dispersion Of The Representation Of Afmentioning
confidence: 99%